Atomic Physics with Accelerators: Projectile Electron Spectroscopy (APAPES) - I. Madesis; A. Dimitriou; A Laoutaris; A. Lagoyannis; M. Axiotis; Mertzimekis, T.; M. Andrianis; S. Harissopulos; E.P. Benis; B. Sulik; I Valastyán; T J M Zouros (Journal of Physics: Conference Series, 2015)
The new research initiative APAPES (http://apapes.physics.uoc.gr/) has already established a new experimental station with a beam line dedicated for atomic collisions physics research, at the 5 MV TANDEM accelerator of the National Research Centre "Demokritos" in Athens, Greece. A complete zero-degree Auger projectile spectroscopy (ZAPS) apparatus has been put together to perform high resolution studies of electrons emitted in ion-atom collisions. A single stage hemispherical spectrometer with a 2-dimensional Position Sensitive Detector (PSD) combined with a doubly-differentially pumped gas target will be used to perform a systematic isoelectronic investigation of K-Auger spectra emitted from collisions of preexcited and ground state He-like ions with gas targets using novel techniques. Our intention is to provide a more thorough understanding of cascade feeding of the 1s2s2p 4 P metastable states produced by electron capture in collisions of He-like ions with gas targets and further elucidate their role in the non-statistical production of excited three-electron 1s2s2p states by electron capture, recently a field of conflicting interpretations awaiting further resolution. At the moment, the apparatus is being completed and the spectrometer will soon be fully operational. Here we present the project progress and the recent high resolution spectrum obtained in collisions of 12 MeV C 4+ on a Neon gas target.